Patterns and trends in horizontal inequality in the Democratic Republic of the Congo - Isaac Kalonda Kanyama (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
We analyse horizontal inequality in wealth and in years of education in the Democratic Republic of the Congo over the period 2001-13. We find that the trend in horizontal inequality is similar to the trend in vertical inequality over the period of analysis. In addition, horizontal inequality in years of formal education is higher among geographical, gender and linguistic groups, and lower among religious and ethnic groups. More specifically, horizontal inequality between genders is higher among individuals aged 25 years and over compared with the full sample of individuals aged 15 years and over. Based on a regression analysis, we find that household size, economic status and rural residence have a significant effect on gender-based inequality in years of education. We also find that gender-based horizontal inequality in years of education is higher in conflict-affected zones.
Keywords: D63; D74; 330; Democratic Republic of the Congo; economic status; education; ethnicity; horizontal inequality; vertical inequality